1998
DOI: 10.1182/blood.v92.9.3098
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Extracorporeal Photochemotherapy in the Treatment of Severe Acute and Chronic Graft-Versus-Host Disease

Abstract: Extracorporeal exposure of peripheral blood mononuclear cells to the photosensitizing compound 8-methoxypsoralen and ultraviolet A radiation has been shown to be effective in the treatment of several T-cell–mediated diseases, including cutaneous T-cell lymphoma and rejection after organ transplantation. We present 21 patients (10 men and 11 women) with hematological malignancies with a median age of 36 years (range, 25 to 55 years) who had received marrow grafts from sibling (n = 12) or unrelated (n = 9) donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
170
0
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 301 publications
(189 citation statements)
references
References 25 publications
15
170
0
4
Order By: Relevance
“…Two patients only had liver involvement with increased hepatic enzymes (patients 2, 3); one also had GI tract cGVHD (patient 3). cGVHD was scored as moderate in three patients (patients 2, 3, 7) and minimal in the other six (patients 1,4,5,6,8,9), who remained off immunosuppressant therapy and continued ECP as sole maintenance treatment [two consecutive days (one cycle) at 1-month intervals].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two patients only had liver involvement with increased hepatic enzymes (patients 2, 3); one also had GI tract cGVHD (patient 3). cGVHD was scored as moderate in three patients (patients 2, 3, 7) and minimal in the other six (patients 1,4,5,6,8,9), who remained off immunosuppressant therapy and continued ECP as sole maintenance treatment [two consecutive days (one cycle) at 1-month intervals].…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the results obtained in our study population, ECP was confirmed to be an effective treatment in patients with steroid-refractory aGVHD grades II-III. 4,[9][10][11] Our choice of limiting the study to patients at these stages was based on evidence from the literature. In particular, Greinix et al 4 obtained encouraging results only in these grades of the disease and not in advanced stages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations